The giver of stars - Moyes, Jojo, 1969- (New York : Random House Large Print, 2019)
"Alice Wright marries handsome American Bennett Van Cleve hoping to escape her stifling life in England. But small-town Kentucky quickly proves equally claustrophobic, especially living alongside her overbearing father-in-law. So when a call goes out for a team of women to deliver books as part of Eleanor Roosevelt's new traveling library, Alice signs on enthusiastically."-- Book jacket.
Keywords: Packhorse librarians -- Fiction; Librarians -- Fiction; Female friendship -- Fiction; Kentucky -- Fiction; Historical fiction; Romance fiction; Large type books